How Do Value Conflicts In Islamic Religious Education Arise Among Muhammadiyah School Students From Nahdatul Ulama Families? - Ramli, Muhammad; Mizani, Hilmi; Ida, Aida (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
The phenomenon of many Nahdlatul Ulama (NU) parents who send their children to Muhammadiyah high schools and vocational high schools raises the potential for religious value conflicts. This study aims to reveal the dynamics of the value conflict in Islamic Religious Education among students. The method employed is a mixed-methods approach with concurrent triangulation, where qualitative and quantitative data are collected simultaneously through questionnaires, interviews, and documentation from students, principals, Islamic Education and Cultivation teachers, and Al-Islam and Muhammadiyah teachers. This research was conducted in six Muhammadiyah schools in Banjarmasin. The results showed that most students experienced conflict between the religious teachings at school and their family traditions, so they tended to be ambivalent about following Muhammadiyah worship practices at school and reverting to NU practices when at home. A small number of students chose to consistently follow Muhammadiyah's teachings even though it caused tension with their parents. The conclusion of this study reveals that the value of Islamic Religious Education in Muhammadiyah schools influences the religious identity of students from NU backgrounds. The implications of this research include input and suggestions related to the concept of inter-religious harmony.